2013
DOI: 10.1073/pnas.1218508110
|View full text |Cite
|
Sign up to set email alerts
|

TLR4–MD-2 complex is negatively regulated by an endogenous ligand, globotetraosylceramide

Abstract: Although endogenous ligands for Toll-like receptor (TLR)4-myeloid differentiation factor 2 (MD2) have not been well-understood, we here report that a globo-series glycosphingolipid, globotetraosylceramide (Gb4), attenuates the toxicity of lipopolysaccharides (LPSs) by binding to TLR4-MD-2. Because α1,4-galactosyltransferase (A4galt)-deficient mice lacking globo-series glycosphingolipids showed higher sensitivity to LPS than wild-type mice, we examined mechanisms by which globo-series glycosphingolipids attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 34 publications
0
53
0
Order By: Relevance
“…When challenged with LPS, A4GALT1 Ϫ/Ϫ mice developed severe inflammation and had significantly higher mortality rates than did wild-type mice (70% versus 10%; P ϭ 0.068). In wild-type mice, LPS upregulated A4GALT1 transcription, leading to increased Gb4 synthesis and expression on cells (393). Furthermore, there was recruitment of TLR4-MD2 into Gb4-enriched GEMs.…”
Section: Globoside and The Innate Immune Systemmentioning
confidence: 95%
See 2 more Smart Citations
“…When challenged with LPS, A4GALT1 Ϫ/Ϫ mice developed severe inflammation and had significantly higher mortality rates than did wild-type mice (70% versus 10%; P ϭ 0.068). In wild-type mice, LPS upregulated A4GALT1 transcription, leading to increased Gb4 synthesis and expression on cells (393). Furthermore, there was recruitment of TLR4-MD2 into Gb4-enriched GEMs.…”
Section: Globoside and The Innate Immune Systemmentioning
confidence: 95%
“…Recently, Gb4 was identified as an endogenous ligand for TLR4-MD2 (393). Preliminary evidence came from studies in A4GALT1 knockout mice, which lack all globo-GSLs (p phenotype) but have normal TLR4-MD2 expression.…”
Section: Globoside and The Innate Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the biological and evolutionary meaning of this extensive variability is still largely unclear [17], the glycans on GSLs are in a favourable position to interact with the lumenal portions of membrane proteins and receptors [18]. Notably, indeed, over the last decades, a number of studies have demonstrated how GSLs influence the behaviour and signalling capability of membrane proteins [2,19,20,21,22,23,24,25,26,27,28,29]. …”
Section: Introductionmentioning
confidence: 99%
“…The specificity of these interactions depends on the precise composition of GSL-glycan sugar residues [20,23,29,89,90,91]. By this virtue, the glycan portion of the GSLs has the potential to interface with specific plasma membrane proteins to modify their activity [2,19,20,21,22,23,24,25,26,27,28,29] by carbohydrate–carbohydrate or protein–carbohydrate interactions [2,29,92]. …”
Section: Introductionmentioning
confidence: 99%